Problems in the Utilization of Educational Technology in Remote Schools - Salsabila, Unik Hanifah; Purwaningrum, Dilla Sekar Ayu; Arrahman, Ahmad Refi (International Journal Labs, 2021)
Background: Education has always been a common conversation that we hear almost every day. The whole world considers education to be a problem that never ends. Because education feels less satisfactory, both in terms of learning and from the way of teaching. Even in developed countries, the problem of disding becomes a very complicated problem.Aim: The purpose of our research is to be able to find out the Problems of Using Educational Technology in Remote Schools, we want to provide an overview of how this educational technology can be used in every circle and during a pandemic that some schools implement online schools using digital media.Method: In this study, we used qualitative methods and library research from several journals and articles.Findings: The results of this study that the Problems of Using Educational Technology in Remote Schools, are still very less than optimal with various obstacles and current conditions. There are still many parents and even teachers complain about the lack of internet network, internet quotas that do not match their needs, and also the parents' lack of understanding with technology